EDUKASI PENANGANAN KETAM KENARI (Birgus latro) YANG DISELAMATKAN OLEH BALAI KONSERVASI SUMBERDAYA DARI PERDAGANGAN ANATAR NEGARA - Agung Setia Agung; M. Ali Ulath; Eko B. Supriyadi; Moh. Taher Anakota; Arif Rahman Basri; Wahyudin Wahyudin; Ferdinando Boger; Christina Situmorang; Intanurfemi B. Hismayasari; Ernawati Ernawati; Asthervina W. Puspitasari (Buletin SWIMP, 2022)
The coconut crab population in the wild has decreased from year to year due to overfishing. One of the purposes of catching is other than for consumption and trading activities in local, national and international markets. On October 19, 2021, the sale of coconut crabs to foreign countries in Malaysia and Hong Kong was prevented by the Sorong City Natural Resources Conservation Center (BKSDA), which at that time was at the Sorong City DEO Airport. The purpose of this activity is to educate the care, maintenance of the coconut crabs that are safe, as well as education of walnut crabs before being released back into the wild. The method of activity in maintaining cocomut crabs is by releasing the coconut crabs in the tub/pond by giving a little ±2 cm of water, then being given shelter, and feeding is done 2 times, in the morning and in the afternoon. Before being released into the wild, the BKSDA conducted socialization to traditional leaders, village heads, heads of marine and fisheries services and the community about the ecosystem and the benefits and status of coconut crabs. The results of the maintenance activities showed that the coconut crabs were in good health and ready to be released into the wild and the community was starting to realize the existence of the coconut crab ecosystem.